Measurement of genetic relation of mithun (Bos frontalis) with other livestock species through RAPD markers - BHUSAN, S; SHARMA, DEEPAK; RAJKHOWA, C (The Indian Journal of Animal Sciences, 2011)
Mithun (Bos frontalis) is found in Northeast hill region ofIndia and adjoining countries of Northeast India. The tribal people rear mithuns for good quality and delicious red meat. Mithun showed maximum genetic similarities with buffalo (0.45), followed by cattle (0.41) and least genetic similarity with goat (0.25). When genetic similarity compared between the large and small ruminants, highest genetic similarity was observed between rnithun with sheep (0.32) and least genetic similarity was between cattle and sheep (0.15). Small ruminants (sheep and goat) expressed highest genetic similarity (0.56) among five species. Moderate genetic similarities were observed between buffalo and cattle (0.39), buffalo and sheep (0.31), buffalo and goat (0.29) and cattle and goat (0.20).Â